Dear friends, Please read our latest blog post for an important announcement about the website. ❤, The Socratic Team

How do you simplify #(sec^2x) - (tan^2x)#?

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

41
Sep 3, 2016

Answer:

#sec^2 x - tan^2 x = 1#

Explanation:

Note that:

#sin^2 x + cos^2 x = 1#

Hence:

#cos^2 x = 1 - sin^2 x#

and we find:

#sec^2 x - tan^2 x = 1/cos^2 x - sin^2 x/cos^2 x#

#color(white)(sec^2 x - tan^2 x) = (1 - sin^2 x)/cos^2 x#

#color(white)(sec^2 x - tan^2 x) = cos^2 x/cos^2 x#

#color(white)(sec^2 x - tan^2 x) = 1#

Was this helpful? Let the contributor know!
1500